1999
DOI: 10.1038/sj.onc.1202687
|View full text |Cite
|
Sign up to set email alerts
|

Etk/Bmx, a PH-domain containing tyrosine kinase, protects prostate cancer cells from apoptosis induced by photodynamic therapy or thapsigargin

Abstract: Prostate carcinoma (PCA) is the most frequently diagnosed malignancy in American men. PCA at advanced stages can both proliferate abnormally and resist apoptosis. Among the many known signal transduction pathways, phosphatidylinositide-3'OH kinase (PI3-kinase) has been shown to play an important role in cell survival and resistance to apoptosis. In this study, we investigate the involvement of Etk/Bmx, a newly discovered tyrosine kinase that is a substrate of PI3-kinase, in protection of prostate cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 40 publications
4
61
1
2
Order By: Relevance
“…For example, Etk has been shown to be a critical mediator of cellular transformation through a cascade link of vSrc-Etk-Stat3 (Tsai et al, 2000) in fibroblast and epithelial cells. Overexpression of Etk stimulates the proliferation of MCF-7 breast cancer cells and protects prostate cancer cells from ionization-and thapsigargininduced apoptosis (Xue et al, 1999;Bagheri-Yarmand et al, 2001). Targeted disruption of Btk has been shown to lead the B cells toward apoptosis (Anderson et al, 1996) and overexpression of Btk in chicken B cells suppresses the Fas-mediated apoptotic signal via the disruption of the FAS-FADD interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Etk has been shown to be a critical mediator of cellular transformation through a cascade link of vSrc-Etk-Stat3 (Tsai et al, 2000) in fibroblast and epithelial cells. Overexpression of Etk stimulates the proliferation of MCF-7 breast cancer cells and protects prostate cancer cells from ionization-and thapsigargininduced apoptosis (Xue et al, 1999;Bagheri-Yarmand et al, 2001). Targeted disruption of Btk has been shown to lead the B cells toward apoptosis (Anderson et al, 1996) and overexpression of Btk in chicken B cells suppresses the Fas-mediated apoptotic signal via the disruption of the FAS-FADD interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Etk plays a pivotal role in IL-6-induced neuroendocrine differentiation and neuropeptide-induced androgen-independent growth of prostate cancer cells (Qiu et al, 1998;Lee et al, 2001). In prostate cancer cells, Etk can be activated by PI-3 kinase and protects LNCaP from radiation-induced apoptosis (Qiu et al, 1998;Xue et al, 1999). Interestingly, upon caspase cleavage, the constitutively activated Etk becomes proapoptotic (Wu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The non-receptor tyrosine kinase Etk/Bmx (epithelial and endothelial tyrosine kinase or bone marrow tyrosine kinase gene in chromosome X), which showed activity in resting LNCaP prostate cancer cells, downstream of PI3-K, provided some protection to these cells from apoptotic death induced by PDT with Pc 4 [84]. However, the mechanism of action of Etk/Bmx in photosensitized cells is not known.…”
Section: Differential Effect Of Pdt On Tyrosine Kinasesmentioning
confidence: 99%
“…Also, expression of CrmA did not affect the kinetics of cytochrome C release Jurkat human lymphoma T cells [295] and procaspase-3 cleavage in a rat/mouse T cell hybridoma sensitized with hypericin [68], suggesting that caspase-8 does not play a major role in the demise process in this model. The activation of caspases in photosensitized cells leads to the cleavage of a number of other cell proteins, including Bap-31 (shuttle protein between the ER and the intermediate compartment and/or Golgi complex [71]), DNA-dependent protein kinase (catalytic subunit) (DNA-PK CS [75]), ICAD (inhibitor of caspase activated DNAse); prevents DNA fragmentation via binding to caspase-activated deoxyribonuclease [76]), focal adhesion kinase (FAK, a kinase involved in the regulation of cell adhesion [73]), lamins (structural components of the nuclear envelope [73]), PARP (poly(ADP-ribose) polymerase, a DNA repair enzyme [18,20,44,54,68,71,72,75,[77][78][79][80][81][82][83][84][85]) and Ras GTPase-activating protein (Ras-GAP, a negative regulator of the Ras signaling pathway [71]). DNA fragmentation in segments that are multiples of 180 -200 bp, another hallmark of apoptotic cell death [86], was also observed in PDT, using different cell types and sensitizers (Table 1).…”
Section: Role Of Caspases In Pdtmentioning
confidence: 99%
“…Our recent ®ndings suggest that Etk/BMX may also be involved in regulation of cell motility (Chen et al, submitted). Aside from and perhaps related to the various physiological and pathological processes they are involved, Btk family of kinases appear to be major regulators of apoptosis (Uckun et al, 1996;Uckun, 1998;Xue, 1999). This will be elaborated further in this review.…”
Section: Introductionmentioning
confidence: 99%